Understanding Barriers to Scaling Up HIV Assisted Partner Services in Kenya - Goyette, Marielle (AIDS Patient Care STDS, 2016)
Assisted partner services (APS) are more effective than passive referral in identifying new cases of HIV in many settings. Understanding the barriers to the uptake of APS in sub-Saharan Africa is important before its scale up. In this qualitative study, we explored client, community, and healthcare worker barriers to APS within a cluster randomized trial of APS in Kenya. We conducted 20 in-depth interviews with clients who declined enrollment in the APS study and 9 focus group discussions with health advisors, HIV testing and counseling (HTC) counselors, and the general HTC client population. Two analysts coded the data using an open coding approach and identified major themes and subthemes. Many participants reported needing more time to process an HIV-positive result before providing partner information. Lack of trust in the HTC counselor led many to fear a breach of confidentiality, which exacerbated the fears of stigma in the community and relationship conflicts. The type of relationship affected the decision to provide partner information, and the lack of understanding of APS at the community level contributed to the discomfort in enrolling in the study. Establishing trust between the client and HTC counselor may increase uptake of APS in Kenya. A client's decision to provide partner information may depend on the type of relationship he or she is in, and alternative methods of disclosure may need to be offered to accommodate different contexts. Spreading awareness about APS in the community may make clients more comfortable providing partner information.